Association of workplace violence and bullying with later suicide risk: a multicohort study and meta-analysis of published data - Hanson Linda L. Magnusson; Pentti Jaana; Nordentoft Mads; Xu Tianwei; Rugulies Reiner; Madsen Ida E.H.; Conway Paul Maurice; Westerlund Hugo; Vahtera Jussi; Ervasti Jenni; Batty G. David; Kivimäki Mika (ELSEVIER SCI LTD, 2025)
Background
Workplace offensive behaviours, such as violence and bullying, have been linked to psychological symptoms, but their potential impact on suicide risk remains unclear. We aimed to assess the association of workplace violence and bullying with the risk of death by suicide and suicide attempt in multiple cohort studies.
Methods
In this multicohort study, we used individual-participant data from three prospective studies: the Finnish Public Sector study, the Swedish Work Environment Survey, and the Work Environment and Health in Denmark study. Workplace violence and bullying were self-reported at baseline. Participants were followed up for suicide attempt and death using linkage to national health records. We additionally searched the literature for published prospective studies and pooled our effect estimates with those from published studies.
Findings
During 1 803 496 person-years at risk, we recorded 1103 suicide attempts or deaths in participants with data on workplace violence (n=205 048); the corresponding numbers for participants with data on workplace bullying (n=191 783) were 1144 suicide attempts or deaths in 1 960 796 person-years, which included data from one identified published study. Workplace violence was associated with an increased risk of suicide after basic adjustment for age, sex, educational level, and family situation (hazard ratio 1.34 [95% CI 1.15-1.56]) and full adjustment (additional adjustment for job demands, job control, and baseline health problems, 1.25 [1.08-1.47]). Where data on frequency were available, a stronger association was observed among people with frequent exposure to violence (1.75 [1.27-2.42]) than occasional violence (1.27 [1.04-1.56]). Workplace bullying was also associated with an increased suicide risk (1.32 [1.09-1.59]), but the association was attenuated after adjustment for baseline mental health problems (1.16 [0.96-1.41]).
Interpretation
Observational data from three Nordic countries suggest that workplace violence is associated with an increased suicide risk, highlighting the importance of effective prevention of violent behaviours at workplaces.
Funding
Swedish Research Council for Health, Working Life and Welfare, Academy of Finland, Finnish Work Environment Fund, and Danish Working Environment Research Fund.